ZnO Powders for Rapid Removal of Cu(II) Ions in Solution - Han, Chengliang; Wang, Genhui; Zhao, Wenlong; Tianran; Chen, Chunhui; Huwei (Asian Journal of Chemistry, 2013)
ZnO powders prepared by direct oxidation of Zn powders were used to remove Cu(II) ions in wastewater. Results showed that the as-prepared ZnO powders had an irregular sheet shape and each sheet was packed with many nanorods. Sorption experimental results indicated that ZnO powders could remove effectively Cu(II) ions in water. The equilibrium sorption isotherm of Cu(II) on ZnO has been analyzed by the Freundlich, Langmuir and Redlich-Peterson isotherm equations.